Pengembangan Pemasaran Sayuran Hidroponik Pada Asosiasi Petani Hidroponik Kabupaten Bondowoso - Rizal Rizal; Ginanjar Mulyo Juniarto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Hydroponic farmers in Bondowoso Regency who are members of the Bondowoso Hydroponic Farmers Association (Astanik), are starting to develop hydroponic vegetable agribusiness to capture opportunities as demand for hydroponic vegetables increases. However, the marketing and promotion carried out by the Bondowosom Hydroponic Farmers Association (Astanik) is still simple. Apart from this, the institutional function of farmers as an organizational forum has not been running optimally, especially in terms of financial recording. Due to these reasons, it is necessary to carry out training in preparing financial reports for the Bondowoso Hydroponic Farmers Association (Astanik). It is also necessary to develop marketing to various parties to expand the marketing reach and sustainability of the hydroponic agribusiness of the members of the Bondowoso Hydroponic Farmers Association (Astanik). Community Learning and Empowerment Practices (COMMMUNITY DEVOTION) will be carried out from December 2022 to March 2023. The results of Community Learning and Empowerment Practices (COMMUNITY DEVOTION) are assistance in preparing digital financial reports for the Hydroponic Farmers Association (Astanik) Bondowoso, marketing development for external parties to obtain a Memorandum of Understanding (MoU) and initiate the opening of a hydroponic vegetable outlet.